Investigation of air temperature on the nightside of Venus derived from VIRTIS-H on board Venus-Express - Migliorini, A; Grassi, D; Montabone, L; Lebonnois, S; Drossart, P; Piccioni, G (2012)
We present the spatial distribution of air temperature on Venus' night side, as observed by the high spectral resolution channel of VIRTIS (Visible and Infrared Thermal Imaging Spectrometer), or VIRTIS-H, on board the ESA mission Venus Express. The present work extends the investigation of the average thermal fields in the northern hemisphere of Venus, by including the VIRTIS-H data. We show results in the pressure range of 100-4. mbar, which corresponds to the altitude range of 65-80. km. With these new retrievals, we are able to compare the thermal structure of the Venus' mesosphere in both hemispheres.The major thermal features reported in previous investigations, i.e. the cold collar at about 65-70°S latitude, 100. mbar pressure level, and the asymmetry between the evening and morning sides, are confirmed here. By comparing the temperatures retrieved by the VIRTIS spectrometer in the North and South we find that similarities exist between the two hemispheres. Solar thermal tides are clearly visible in the average temperature fields. To interpret the thermal tide signals (otherwise impossible without day site observations), we apply model simulations using the Venus global circulation model Venus GCM (Lebonnois, S., Hourdin, F., Forget, F., Eymet, V., Fournier, R. [2010b]. International Venus Conference, Aussois, 20-26 June 2010) of the Laboratoire de Météorologie Dynamique (LMD). We suggest that the signal detected at about 60-70° latitude and pressure of 100. mbar is a diurnal component, while those located at equatorial latitudes are semi-diurnal. Other tide-related features are clearly identified in the upper levels of the atmosphere. © 2011 Elsevier Inc.